Research on reflection characteristics of the terahertz channel for 6G - Pan TANG; Jiaxin LIN; Jianhua ZHANG; Lei TIAN; Zhaowei CHANG; Liang XIA; Qixing WANG (Tongxin xuebao)
The reflection characteristics of the terahertz channel are crucial for understanding and mastering the propagation mechanism of the terahertz channel, which are also required for a high-precision terahertz channel model for 6G.Therefore, the research status of terahertz channel reflection characteristics in theoretical modeling and measurement analysis were first summarized.Then, the reflection coefficient measurement campaign in the frequency range of 240 GHz to 310 GHz for five kinds of common building materials was conducted by a time-domain correlation-based terahertz channel measurement platform.It was found that the reflection coefficients were related to the incident angle.Based on the Rayleigh reflection coefficient theoretical model, a statistical reflection coefficient model was further proposed as a function of incident angle.Generally, the proposed model could accurately describe the variation law of the reflection coefficient with angle.Finally, research directions of terahertz channel reflection characteristics were discussed.